Post LASIK progressive astigmatism in a child with partially accommodative esotropia - Suma, G; Mathur, U; Sethi, S; Arora, P; Garg, J (Nepalese Journal of Ophthalmology, 2013)
Introduction: Refractive surgery is considered a safe and effective method for correction of refractive errors in adults. Objective: To report an unusual case of a young child with partially accommodative esotropia presenting with deterioration of vision and worsening of esotropia following refractive surgery. Case report: Unanticipated and progressive irregular corneal astigmatism along with deterioration of visual acuity and loss of stereopsis developed post- LASIK in a seven-year-old Indian child with partially accommodative esotropia. Conclusion: Keratorefractive surgery in young children has to be undertaken with caution, especially in such cases where there is no medical indication for refractive surgery and waiting beyond teenage years is a viable option. Nepal J Ophthalmol 2013; 5(9):109-113 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7836